Electrocatalytic and Electroanalytic Investigation of Carbohydrates Oxidation on Gold-Based Nanocatalysts in Alkaline and Neutral pHs. Issue 9 (31st May 2018) - Holade, Yaovi; Engel, Adriana Both; Servat, Karine; Napporn, Teko W.; Morais, Cláudia; Tingry, Sophie; Cornu, David; Kokoh, K. Boniface
Abstract : The design and fabrication of durable nanocatalysts to efficiently and selectively electro-oxidize organic molecules toward value-added product(s) is an important starting point for the future deployment of electrochemical "cogeneration" devices with the triple advantage of producing electricity, heat and fuels/chemicals. This interdisciplinary research requires a synergistic effort from three communities of electrochemistry/electrocatalysis, material science and organic chemistry. To this end, we chose to explore the integration of different electrochemical and analytical techniques to study the outstanding ability of gold-based nanomaterials in the electrocatalytic oxidation of mono- and di-saccharides. In order to rationalize the previous outcomes on the selective catalysts for glucose-to-gluconate conversion toward cogenerating organic electrosynthesis (ECS Trans., 77, 1547 (2017)), a multivariate study is carried out in alkaline and neutral pHs by examining three substrates, glucose, galactose, lactose and different electrodes. Electroanalytical investigation revealed that these substrates are selectively oxidized at their C1-position (two transferred electrons). At pH 7.4, the corresponding lactone and acid forms were detected by their specific vibration bands of 1744 and 1780 cm −1, which is explained by a local pH decrease within the thin-electrolyte. Our study delineates a broad strategy for organic electrosynthesis in electrochemical cells by controlling electrode materials fabrication.